Subsequent Injury Study (SInS): Improving outcomes for injured New Zealanders. Issue 6 (20th October 2016) - Derrett, Sarah; Harcombe, Helen; Wyeth, Emma; Davie, Gabrielle; Samaranayaka, Ari; Hansen, Paul; Hall, Gill; Cameron, Ian D; Gabbe, Belinda; Powell, Denise; Sullivan, Trudy; Wilson, Suzanne; et al.
Abstract : Background: Subsequent injury (SI) is a major contributor to disability and costs for individuals and society. Aim: To identify modifiable risk factors predictive of SI and SI health and disability outcomes and costs. Objectives: To (1) describe the nature of SIs reported to New Zealand's no-fault injury insurer (the Accident Compensation Corporation (ACC)); (2) identify characteristics of people underaccessing ACC for SI; (3) determine factors predicting or protecting against SI; and (4) investigate outcomes for individuals, and costs to society, in relation to SI. Design: Prospective cohort study. Methods: Previously collected data will be linked including data from interviews undertaken as part of the earlier Prospective Outcomes of Injury Study (POIS), ACC electronic data and national hospitalisation data about SI. POIS participants (N=2856, including 566 Māori) were recruited via ACC's injury register following an injury serious enough to warrant compensation entitlements. We will examine SI over the following 24 months for these participants using descriptive and inferential statistics including multivariable generalised linear models and Cox's proportional hazards regression. Discussion: Subsequent Injury Study (SInS) will deliver information about the risks, protective factors and outcomes related to SI for New Zealanders. As a result of sourcing injury data from New Zealand's 'all injury' insurer ACC, SInS includes people who have been hospitalised and not hospitalised for injury. Consequently, SInS will provide insights that are novel internationally as other studies are usually confined to examining trauma registries, specific injuries or injured workers who are covered by a workplace insurer rather than a 'real-world' injury population.